Application of Cow Manure to Improve Soil Chemical Characteristics and Promote Vegetative Growth of Oil Palm (Elaeis guineensis Jacq.) Seedling on Sub Soil Media - Hidayat, Fandi; Syarovy, Muhdan; Pradiko, Iput; Rahutomo, Suroso (Jurnal Penelitian Kelapa Sawit, 2020)
Standard media for oil palm seedling is top soil with sufficient content of organic matter. However, in certain locations such as mineral marginal land where the top soil has been heavily eroded, top soil will be scarcely available. Under these con-ditions, sub soil might be used for seedling media. Physical, chemical, and biological characters of sub soil usually are not suitable for seedling media, but it might be corrected by applying soil amendment. The aim of this study is to identify the effects of combination of soil amendment in the form of cow manure (notated as “O”, in the level of 0 and 5%) and the standard of inorganic fertilization (notated as “S”, in the level of 0, 25, 50, 75, and 100%) on the changes of chemical properties of sub soil media and vegetative growth of oil palm seedlings. The experiment was arranged in a Randomized Completely Block Design employing 7 treatments i.e. control (O0S0), standard inorganic fertilizers (O0S100), and 5 treatments which were the combination of 5% (by weight of the soil media) of cow manures and several levels of inorganic standard fertilizing (O5S0, O5S25, O5S50, O5S75, and O5S100). The results revealed that, application of 5% cow manures has improved the organic matter content, cation exchange capacity, and available nutrients in the sub soil seedling media. Though O5S50 (combination of 5% cow manure and 50% standard inorganic fertilizing) resulted in Relative Agronomic Effectiveness (RAE) which was higher than 100%, the best performance of oil palm seedlings growth was under treatment of O5S50 (the combination of 5% cow manure and 100% standard inorganic fertilizing).